Internal Quality Assurance Management as a Strategy for Achieving National Education Standards through The Principle of Continuous Improvement - Habibi, Habibi; Arismunandar, Arismunandar; Rahman, Abdul; Darmawangsa, Andi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the implementation of internal quality assurance management in achieving national education standards through continuous improvement at MAN Insan Cendikia Gowa and SMA Islam Athira Makassar. This research uses a qualitative research approach with a case study approach. The results showed that the implementation of internal quality assurance management on the principle of continuous improvement at MAN Insan Cendikia Gowa and SMA Islam Athirah Makassar was carried out based on the fulfillment of the Eight National Education Standards by conducting continuous evaluations through school self-evaluation involving all parties to move towards achieving quality higher education is not surprising that the two institutions are one of the only secondary education institutions and have become the educational institution of choice for the community.